ШВИДКІСТЬ ЗРОСТАННЯ ФІТОПЛАНКТОНУ І ЙОГО СПОЖИВАННЯ МІКРОЗООПЛАНКТОНОМ В ПЕРІОД ОСІННЬОГО “ЦВІТІННЯ” EMILIANIA HUXLEYI В ЗАПАДНІЙ ЧАСТИНІ ЧОРНОГО МОРЯ - Стельмах, Л. В.; Куфтаркова, Є. А.; Бабіч, І. І. (Marine Ecological Journal, 2023)
The studies were carried out in the western part of the Black Sea in October – November 2010 during the 67 th and 68 th of scientific expeditions on the research vessel "Professor Vodyanitsky." For surface waters of the sea large spatial variability of the specific phytoplankton growth rate and microzooplankton grazing was obtained. The dependence of these parameters on the taxonomic structure of the phytoplankton was revealed. The autumn bloom of Emiliania huxleyi was registered in surface waters. Weak microzooplankton grazing of phytoplankton has been one of the main causes of this phenomenon.